PENGARUH METODE SOSIODRAMA TERHADAP PERILAKU SOPAN SANTUN SISWA MAN 3 BANTUL - Akhmad Muzaki; Casmini Casmini (UIN Sunan Kalijaga Yogyakarta, 2019)
ABSTRACTPoliteness among students begin to decline, phenomenon occured in schools many students who do not understand the behavior of courtesy in relationships in the school environment. Therefore, guidance and counseling services are expected to overcome this phenomenon. This research intend to find out and analyze the effect of sociodrama method on students manners. The type of research is experimental research with research subjects totaling 15 students. Data collection technique uses courtesy scale, observation, interview and documentation. In addition, data analysis technique uses paired samples test (T-test). The results of data analysis obtained from the average pretest score is 138,40 while the average posttest score is 143,67. Based on these data show that there is an average increase of -5,267. Correlation value obtained from paired samples test (T-test) is 0,915 with significant 0,000. T-count Value is -3,088 with sig. (2-tailed) value is 0,008. T-count (-3,008) ≥ t-table (2,145) and sig. (2-tailed) value is 0,008 ≤ 0,05. These data mean that Ha in this research is accepted and Ho is rejected so that there are different an average manners before and after treatment (sociodrama method). Thereby, sociodrama method influences the behavior of student’s manners MAN 3 Bantul.Keywords: Sociodrama Method, The Behavior of Courtesy